British University Libraries, 1st edition - Burrows, Toby (Routledge, 2020)
British university libraries face major financial, technological, and organizational challenges. Cuts in funding, the spread of new technology, and changes to the provision of university education as a whole are combining to fundamentally alter the circumstances in which university libraries operate. This book, first published in 1989, provides a thorough understanding of the major trends that have emerged during the past decade and projects them into the future to assess their likely effect over the next few years. By focusing on the most important developments in the areas of finance, staffing, collections, services, automation, and relations with other libraries, author Toby Burrows exposes the forces that threaten the very nature of the British university library. The changes affecting British universities as a whole are also analysed since these broad influences have been a major cause of change in libraries and are essential to an understanding of that change. The future of the British university library depends on its ability to clearly articulate a coherent vision of its own future; this book takes a crucial step toward this goal.